Foreign Debt, Capital Controls, and Secondary Markets: Theory and Evidence from Nazi Germany - Papadia, Andrea; Schioppa, Claudio A. (Journal of Political Economy, 2024)
We investigate how internal distribution motives can affect the implementation of an important macroeconomic policy: capital controls. To do this, we study one of history’s largest debt repatriations, which took place under strict capital controls in 1930s Germany, providing a wealth of quantitative and historical evidence. We show that the authorities kept private repatriations under strict control, thus avoiding detrimental macroeconomic effects, while allowing discretionary repatriations in order to reap internal political benefits. We formalize this mechanism in a model in which elite capture can affect optimal debt repatriations and the management of official reserves under capital controls.